The role of educational technologies in improving management effectiveness - Amonova, Nodira (MMIT Proceedings, 2025)
This article thoroughly analyzes the significance of educational technologies in management, their current state, foreign experience in implementing educational technologies to improve management effectiveness, the impact of educational technologies on management effectiveness, methods of their use, and their significance in improving efficiency. The possibilities of using educational technologies in increasing the effectiveness of management activities and its advantages have been scientifically investigated. The possibilities of applying educational technologies in management and assessing their effectiveness are theoretically highlighted.